A Simple Bayesian Method for Evaluating Whether Data From Patients With Rheumatic Diseases Who Have Been Under Chronic Hydroxychloroquine Medication Since Before the COVID-19 Outbreak Can Speak to Hydroxychloroquine's Prophylactic Effect Against Infection With SARS-CoV-2 - Musca, Serban C. (Frontiers in Medicine, 2020)
No vaccine against infection by SARS-CoV-2 exists yet. Among others treatments, hydroxychloroquine (HCQ) medication has been proposed. However, prophylactic HCQ medication has hardly been evaluated. We propose to use data from patients with rheumatic diseases (RA, SLR) who have been chronically taking HCQ medication since before the COVID-19 outbreak (hereafter: HCQpa), in order to evaluate HCQ's potential to prevent infection with SARS-CoV-2. This can be achieved with relative ease by considering whether COVID-19 prevalence is significantly lower in HCQpa than in the general population (i.e., all people that are not HCQpa). Even if COVID-19 prevalence is truly significantly lower in HCQpa, some HCQpa may still present with COVID-19 (lower prevalence does not mean a prevalence of zero). However, given a COVID-19 prevalence value in the general population and a number of available HCQpa, one may compute the maximum number of HCQpa for that total number of HCQpa considered that can have COVID-19 in order to still be able to conclude to a lower COVID-19 prevalence in the HCQpa (i.e., one more case of COVID-19 than that maximum number and the COVID-19 prevalence in the HCQpa cannot be said anymore to be lower than in the general population). Because the COVID-19 prevalence in the general population is not known with precision, we will consider different general population prevalence values. Among these contemplated prevalence values, one is derived from the official total number of confirmed cases, others by computing the total number of cases from the number of fatal COVID-19 cases so far and considering different case fatality rate per total cases. Our analyses show that systematic testing for COVID-19 in as few as 5,000 HCQpa is all that is needed for a test of whether HCQ has a prophylactic role against COVID-19, even for a COVID-19 prevalence value as low as 250 per 100,000, provided the test's sensitivity is at least equal to its specificity. For higher COVID-19 prevalence values, the number of HCQpa needed is even lower.